Nutrition and epigenetics: An interplay of dietary methyl donors, one-carbon metabolism, and DNA methylation - Anderson, Olivia S. (2012)
DNA methylation is the most extensively studied mechanism of epigenetic gene regulation. Increasing evidence indicates DNA methylation is labile in response to nutritional and environmental influences. Alternations in DNA methylation profiles can lead to changes in gene expression, resulting in diverse phenotypes with the potential for increased disease risk. The primary methyl donor for DNA methylation is S-adenosylmethionine (SAM), a species generated in the cyclical cellular process called one-carbon metabolism. One-carbon metabolism is catalyzed by several enzymes in the presence of dietary micronutrients, including folate, choline, betaine, and other B vitamins. For this reason, nutrition status, particularly micronutrient intake, has been a focal point when investigating epigenetic mechanisms. Though animal evidence linking nutrition and DNA methylation is fairly extensive, epidemiological evidence is less comprehensive. This review serves to integrate studies of the animal in vivo with human epidemiological data pertaining to nutritional regulation of DNA methylation, and to further identify areas in which current knowledge is limited.